Pollution and radiological risk assessments of mine wastes from selected legacy and active mines in the Philippines - Cris Reven Gibaga; Jessie Samaniego; Alexandria Tanciongco; Rico Neil Quierrez; Mariel Montano; John Henry Gervasio; Rachelle Clien Reyes; Monica Joyce Peralta (Brawijaya University, 2022)
In the Philippines, legacy mines and active mine wastes pose potential threats since these may contain elevated concentrations of potentially toxic elements (PTEs) and high natural radioactivity. In this study, legacy mine wastes from the Philippine Iron Mine (PIM), Barlo Mine (BM), and Rapu-Rapu Mine (RRM) and active mine tailing from Padcal Mine (PM) were analyzed to determine the concentrations of fifteen (15) PTEs and the activity concentrations of natural radionuclides. Several quantitative risk indicators and radiological health risk parameters were utilized to determine the potential effects of these mine wastes to the natural environment and to human health. Legacy mine wastes have higher contents of PTEs and are more polluted by PTEs than PM tailing. Both enrichment factor (EF) and geoaccumulation index (Igeo) values suggest that legacy mine wastes are strongly polluted by As, Cd, Cu, and Mo. BM and RM wastes are also polluted by Pb, Sb, and Zn; PIM waste is polluted by Ni and V; and BM waste is polluted by Tl. Padcal mine tailing is only moderately polluted by Cu and Mo. The natural radionuclide activity concentrations of legacy and active mine wastes are below the global background values and the radiological hazard indices are also all lower than their permissible limits, except for 40K, 238U, and absorbed gamma dose rate in PIM due to a geogenic source. Unlike the PTEs, radioactivity in the legacy and active mine wastes are not enhanced by mining activities and is not a significant risk factor to human health.